Star-poly(ε-caprolactone) as the stationary phase for capillary gas chromatographic separation. Issue 49 (13th September 2019) - Sun, Tao; Jiang, Xingxing; Song, Qianqian; Shuai, Xiaomin; Chen, Yujie; Zhao, Xinyu; Cai, Zhiqiang; Li, Ke; Qiao, Xiaoguang; Hu, Shaoqiang
Abstract : This work presents the separation performance of star-poly(ε-caprolactone) (star-PCL) as the stationary phase for capillary gas chromatography (GC). Abstract : This work presents the separation performance of star-poly(ε-caprolactone) (star-PCL) as the stationary phase for capillary gas chromatography (GC). The statically coated star-PCL column showed a column efficiency of 3345 plates per m and moderate polarity. Importantly, the star-PCL column exhibited high selectivity and resolving capability for more than a dozen mixtures covering a wide-ranging variety of analytes and isomers. Among them, the star-PCL column displayed advantageous resolving capability over the commercial DB-1701 column for aromatic amine isomers such as toluidine, chloroaniline and bromoaniline. Moreover, it was applied for the determination of isomer impurities in real samples, showing good potential in GC applications.